Oral communication strategies among Malaysian L2 learners in oral communicative learning - Gan, Lai Kuen (2017)
Learners should consciously use their cognition system to control their performance in oral communication and to maintain their interactions with others. Hence, in order to achieve these goals, learners’ strategic competence can be developed by raising their awareness on specific oral communication strategy use and encourage independent learning skills through metacognitive strategies for future target language context. Therefore, this study involves three phases whereby in the first phase, it focuses on investigating the different learning strategies used by polytechnic students in Malaysia which provides a baseline for decisions made to develop a training module in the second phase. In the third phase, this study identifies the types of oral communication strategies used by students and also examines to what degree do metacognition strategies and oral communication strategies could be explicitly taught to enhance oral communication abilities and confidence. Due to many students still unaware of their learning strategies and the correct strategies relevant to overcome breakdown in communication, this study aims to raise learners’ awareness of strategies that might be used to solve communication problems through the use of strategy embedded module; investigate how communicative strategy training affect students speaking proficiency; and how do learners perceive and use their strategies in class and beyond the classroom for independent learning. This quasi experimental study uses multiple method of data collection with two sets of questionnaires adapted from Oxford’s Strategy Inventory Language Learning (SILL; 1990), Oral Communication Strategy Inventory (OCSI) by Nakatani (2010), a pre and post test oral communication test for the experimental and control group, as well as a strategy diary. Data was triangulated qualitatively and tabulated quantitatively using the SPSS version 22 software, Transana 3.01 and Atlas.ti to analyse students’ performance and also used the independent sample t-test and ANOVA to determine the impact of strategy training on the learners’discourse. The findings show positive results of communication strategies used by learners such as fillers, asking for repetition, confirmation checks, fluency-oriented, negotiation for meaning and accuracy-oriented strategies. In addition, the strategy training had helped the learners to be more strategic competent and improve on their performance in learning and communicating in English. This study indicated that communication strategy could be used to help learners to solve communication difficulties and enhance their confidence during interactions with others.